Understanding the Integration of Socio-Technical Actors for Sharing and Sustainable Urban Mobility - Carlos Henrique T. Pereira; Minelle E. Silva (BBR: Brazilian Business Review)
In the search for sustainability and urban reconfiguration, this research analyzes a business model used in sustainable urban mobility initiatives that integrates public and private agents (socio-technical actors - ST-actors) in Fortaleza (Brazil). An integrated case study was carried out with two initiatives: VAMO Fortaleza (e-carsharing) and Bicicletar (bike sharing). Interviews were conducted with the protagonist ST-actors, and documents were analyzed focusing on shared urban mobility. We observed that the initiative implementation integrates ST-actors through public-private partnerships. Based on that, a schematic model was designed to illustrate ST-actor integration as a business model that can be replicated in other contexts using sharing economy principles. In the context of the urban mobility reconfiguration focused on sustainability, we explore a case which has been internationally recognised and we present an underexplored theme about sharing economy initiatives that can be practised.